Susceptibility of the blowfly, Chrysomya putoria (Diptera: Calliphoridae) to the ethanolic extracts of the medicinal plant Moringa oleifera (Magnoliopsida: Moringaceae) - Bastos Sant’Ana da Silva Terto, Agatha; Leal Caetano, Rebecca; Carriço , César; Maria dos Santos, Michele; Vianna Barbosa, Júlio; Augusto Albuquerque dos Santos, José; Teixeira Pinto, Zeneida (Revista Colombiana de Entomología, 2024)
Topical administration of Moringa oleifera leaf and seed ethanolic extracts concentrations (5, 10, 25, 50, 75, and 100 mg/L) were screened for insecticide activities against Chrysomya putoria (Diptera: Calliphoridae). Results showed that all tested leaf and seed extractconcentrations were toxic, delayed post-embryonic larval development, and reduced weight. As for C. putoria mortality, from newly hatched larvae to the adult period, all concentrations showed larvicidal power. However, above 20% of the mortality rate occurred in those treated with both leaf and seed extract concentrations. The ones treated with M. oleifera leaf extract concentrations presented the respective mortality rates: 50 mg/L (23 %), 75 mg/L (29 %), and 100 mg/L (30 %). While those treated with M. oleifera seed extract concentrations, the mortality rate observed was 25 mg/L (20 %), 50 mg/L (27 %), 75 mg/L (30 %), and 100 mg/L (32 %). The medicinal plant M. oleifera leaf and seed extracts proved to be a viable alternative for the population control of the medical veterinary and sanitary important blowfly C. putoria.